1998
DOI: 10.1161/01.hyp.31.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight Versus Childhood Growth as Determinants of Adult Blood Pressure

Abstract: Abstract-In older white American adults, recent retrospective studies have demonstrated a relationship between lower birth weight and hypertension. Black Americans have a higher occurrence of both lower birth weight and hypertension than do white Americans. To test the low birth weight-high blood pressure hypothesis, data from a prospective study (Perinatal Collaborative Project) were examined. The study followed a sample of 137 black Americans, with nine examinations. Data on birth weight, growth, and blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…The insignificant correlation between birth weight and SBP in black children in the present study is similar to previous studies in black children, 22 adolescents, 6,7 and adults. 23 Furthermore, high rather than low birth weight may be related to a higher blood pressure in late pubertal black children as shown in the current study and one previous study. 8 Previous studies have shown that high birth weight may be associated with increased risk of diabetes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The insignificant correlation between birth weight and SBP in black children in the present study is similar to previous studies in black children, 22 adolescents, 6,7 and adults. 23 Furthermore, high rather than low birth weight may be related to a higher blood pressure in late pubertal black children as shown in the current study and one previous study. 8 Previous studies have shown that high birth weight may be associated with increased risk of diabetes.…”
Section: Discussionsupporting
confidence: 73%
“…37,38 Thus, parent-reported birth weights were used in numerous previous studies. 23,30,33,36 In addition, the sample size at our baseline survey was relatively small, particularly for black children; therefore, cautions may be needed for interpreting the nonsignificant association between birth weight and SBP among black children. However, our results were in agreement with that of previous studies, which reported nonsignificant relations of birth weight to SBP among black children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The associations in different populations and different age groups have been weaker or not detected. 10 Fagerudd et al provide a significant contribution to this body of literature with this study and confirmatory data regarding the increased risks of elevated blood pressure and diabetes in individuals with low birth weight. 1 In addition, these investigators find a strong association of low birth weight with elevated systolic blood pressure, the blood pressure with the greatest cardiovascular disease risks.…”
Section: Implications For Studysupporting
confidence: 83%
“…43,44 Follow-up of a random stratified sample of UK children examined in 1935-37 found an inverse association between childhood height and blood pressure in late adulthood. 45 Leg length was the component of height that was most strongly related to blood pressure (D Gunnell, personal communication), but this effect was not seen in a cohort of adult males, despite the inverse association between leg length and CHD incidence.…”
Section: Explanation Of Trendsmentioning
confidence: 99%